Developing guidelines for early detection of child and adolescent mental health problems - Nandy Agustin Syakarofath; Falistya Roisatul Mar'atin Nuro; M. Karimun (Journal of Community Service and Empowerment, 2023)
Children, like adults, can suffer from various mental health issues, but they are rarely recognized. This research aims to create early detection guidelines that can be used by those closest to children, such as parents and teachers in schools. The methods used by the team were narrative review, data analysis, preparation of guidelines, expert judgment, and dissemination. Three experts carried out the preparation of the guide. Furthermore, the dissemination was carried out at SDN Girimoyo 02 Karangploso, Malang Regency. The guideline contains six points, namely 1) definition of mental health, 2) description of the child's mental health issues, 3) description of instruments that can be used for screening or early detection, 4) various considerations that need to be considered when conducting screening or early detection, 5) referral system and flow, and 6) the role of teachers in schools and their urgency. Furthermore, the result of the dissemination activity is the increased understanding of teachers in schools regarding the early detection of student's mental health problems so that teachers can be more sensitive to the conditions of their students.